PENDAMPINGAN IDENTIFIKASI PUSAKA BUDAYA DESA BALI AGA BELANDINGAN KINTAMANI BANGLI - Ni G.A. Diah Ambarwati Kardinal; I Gusti Ayu Ketut Artatik; I Putu Sarjana (JURNAL SEWAKA BHAKTI, 2019)
Belandingan is the village of Bali Aga mountain type located in Kintamani District, Bangli Regency, Bali. The location of Belandingan Village itself is quite secluded compared to other villages around Batur. Mount Batur was named the world geopark by UNESCO on 22 September 2013. Belandingan Village is included in 15 Batur Geopark Supporting villages. Although it has become a Supporting Village of Batur Geopark, there is not tourism planning done by the government. Research on the Village of Blandingan itself is difficult to find. The distinctive cultural richness of the Bali Aga Village has the potential for the development of a heritage Tourism Village. The character of Belandingan Village community that is friendly and open to outsiders is also a potential in promoting the tourism of the village. Existing traditions are still in verbal version. The community has not been moved to document their culture. The people themselves when invited to discuss are less aware of the cultural uniqueness they have. For this reason, assistance was provided to the community in this case the religious leaders in the village of Belandingan and Sekaa Teruna Teruni Mandala Cipta Belandingan Village to identify village heritage. It is hoped that the results of this identification will become written data and become material in promoting the field of tourism as a Bali Aga tourist village.